Concept, essence and main problems of a legal regulation of the international jurisdiction - Romanova, Olga N. (Journal of the Belarusian State University. Law, 2019)
Article is devoted to the analysis of concept and essence of the international jurisdiction of a civil procedural and economic procedural law. Questions of a conceptual framework of this institute are investigated: ratios of the concepts «international jurisdiction», «cognizance», «jurisdiction», and also main problems of legal regulation. Need of use of different terminology for designation of a competence of the courts of Republic of Belarus locates in interstate sense (jurisdiction, cognizance) and a competence of the courts on affairs with a foreign element. The author suggests to refer observance of rules of the international jurisdiction to conditions of realization of the right for presentation of the claim and to establish in procedural codes corresponding a consequences of non-compliance with the specified rules.
Keywords: transnational civil procedure; international jurisdiction; competence; cross-border civil cases